2018
DOI: 10.1186/s12874-018-0537-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-selection in a population-based cohort study: impact on health service use and survival for bowel and lung cancer assessed using data linkage

Abstract: BackgroundIn contrast to aetiological associations, there is little empirical evidence for generalising health service use associations from cohort studies. We compared the health service use of cohort study participants diagnosed with bowel or lung cancer to the source population of people diagnosed with these cancers in New South Wales (NSW), Australia to assess the representativeness of health service use of the cohort study participants.MethodsPopulation-based cancer registry data for NSW residents aged ≥4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…19,26 45 and Up Study participants diagnosed with lung cancer were less socio-economically disadvantaged, healthier and less likely to live in major cities than all NSW residents aged ≥45 years diagnosed with lung cancer. 27 Hospital and emergency department use in the year prior to lung cancer diagnosis were similar between 45 and Up Study participants and all NSW residents; however, primary and outpatient care use could not be assessed. 27 Participants of cohort studies may differ from non-responders in their health literacy and health-seeking behaviours.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…19,26 45 and Up Study participants diagnosed with lung cancer were less socio-economically disadvantaged, healthier and less likely to live in major cities than all NSW residents aged ≥45 years diagnosed with lung cancer. 27 Hospital and emergency department use in the year prior to lung cancer diagnosis were similar between 45 and Up Study participants and all NSW residents; however, primary and outpatient care use could not be assessed. 27 Participants of cohort studies may differ from non-responders in their health literacy and health-seeking behaviours.…”
Section: Discussionmentioning
confidence: 88%
“…27 Hospital and emergency department use in the year prior to lung cancer diagnosis were similar between 45 and Up Study participants and all NSW residents; however, primary and outpatient care use could not be assessed. 27 Participants of cohort studies may differ from non-responders in their health literacy and health-seeking behaviours. This may result in differences in diagnostic pathways compared with the general NSW population with lung cancer.…”
Section: Discussionmentioning
confidence: 88%
“…However, we derived excess cancer costs by comparing individuals within the cohort and adjusted for key factors in regression analyses. A recent paper from the 45 and Up Study reported that study participants diagnosed with lung cancer had longer post-diagnosis survival, but the cohort had similar levels of hospital and ED use as the NSW population [41]. Furthermore, our cohort was comparable to the total population of lung cancer cases on most key factors.…”
Section: Discussionmentioning
confidence: 50%
“…While 45 and Up Study participants are healthier on average than the general population, relative estimates calculated from within-cohort comparisons are valid. [34,35] Two data issues are also unlikely to have affected our within-cohort comparisons; firstly, the ED data mainly captured visits to metropolitan and large regional public hospitals (72% and 88% of ED presentations in NSW, respectively). [36,37] Secondly, some pathology services will be under-ascertained as MBS claims data only capture the three most expensive pathology items in an episode of care performed by a GP.…”
Section: Plos Onementioning
confidence: 99%
“…MBS item numbers 2, 3,23,35,36, 44, 52, 53, 54, 57, 2501, 2504, 2517, 2521, 2525, 2546, 2552, 2721, 2725, 5000, 5020, 5040, 5060). We further distinguished GP consultations for the preparation, contribution or review of a GP management plan or multidisciplinary/team care plan (MBS item numbers 721,723, 729, 731, 732, 735, 739, 743, 747, 750, 758, 820, 822, 823, 825, 826, 828, 830, 832, 834, 835, 837, 838, 900)…”
mentioning
confidence: 99%